Unnecessary Force by Police: Insights from Evolutionary Psychology. (5th April 2018) - James, Lois; Todak, Natalie; Savage, Joanne
Abstract: The police function in modern society is grounded in the legitimate authority to use force to produce an overall increase in public safety. This authority is granted by a social contract between the police and citizenry, and predicated on the public's faith that the police will not abuse these powers. The police profession is at a critical juncture, due in large part to public concerns about excessive and discriminatory use of force by police. The dual expectations of aggression and restraint must be expertly balanced in policing, but this balance can be challenging given the dangerous realities of, and the increasingly critical atmosphere surrounding, the police profession. In this article, we apply evolutionary psychological theory to understand: (1) why aggression is often a selected response and (2) how restraint may be encouraged in policing contexts. We propose specific recommendations for police training and practice.